2022
DOI: 10.1097/med.0000000000000759
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of androgen abuse: a review of the HAARLEM study

Abstract: Purpose of reviewData on the health effects of androgen abuse are mainly derived from lower level evidence, such as case series and cross-sectional studies. In the last few years a relatively large and prospective cohort initiative, the HAARLEM (health risks of anabolic androgenic steroid use by male amateur athletes) study, made an important contribution to current knowledge. Recent findingsThe HAARLEM study showed that all androgen abusers experience positive and negative effects, such as an increase in stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Creatinine concentrations returned to baseline after cessation of use. Albuminuria, as measured by dipstick analysis, emerged or increased in 16% of the subjects (155). A larger increase in serum creatinine levels was observed in a small 4-week placebo-controlled trial with resistance-trained men randomized to 330 mg daily of the oral prohormone 3bhydroxy-5a-androst-1-en-17-one (1-androsterone) or placebo (38).…”
Section: Nephrotoxicitymentioning
confidence: 98%
“…Creatinine concentrations returned to baseline after cessation of use. Albuminuria, as measured by dipstick analysis, emerged or increased in 16% of the subjects (155). A larger increase in serum creatinine levels was observed in a small 4-week placebo-controlled trial with resistance-trained men randomized to 330 mg daily of the oral prohormone 3bhydroxy-5a-androst-1-en-17-one (1-androsterone) or placebo (38).…”
Section: Nephrotoxicitymentioning
confidence: 98%
“…Most of the evidence about the effects of AAS on urological and andrological parameters comes from controlled environmental settings, such as administering a single AAS compound under a known dosage ( Bond et al, 2022 ). However, the abovementioned situation does not reflect the reality of most AAS abusers, who usually adopt a polypharmacy strategy to maximize physical performance gains while counteracting any harmful and undesired aesthetic side effects ( Smit et al, 2020 ; Bond et al, 2022 ; Smit et al, 2022 ). For example, recent findings ( Smit et al, 2020 ) have demonstrated that AAS users may utilize a median of five different AAS substances during the cycle (i.e., period of AAS usage), with a range of one to eleven different substances, totaling a median of 901 mg of testosterone per week (i.e., range 250–3,382 mg) over 13 weeks of AAS-cycle duration (i.e., range 2–52 weeks).…”
Section: Brief Background and Current Characteristics Of Aas Usementioning
confidence: 99%
“…It was not long ago that those abusing androgens were told that they were not actually effective [ 90 ], while the risks of their use and abuse may have been exaggerated [ 91 , 92 , 93 , 94 , 95 ]. Nevertheless, it should be acknowledged that potential risks with long-term abuse exist, especially with respect to adverse cardiovascular effects [ 96 ], while the health effects associated with long-term TRT use are still being investigated [ 97 ].…”
Section: Observational Studiesmentioning
confidence: 99%